PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SD - Amelia Margaretha Tampubolon; Reflina Sinaga; Antonius Remigius Abi; Darinda Sofia Tanjung; Ester Julianda Simarmata; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research aims to determine the effect of the Student Team Achievement Division Type Cooperative Learning model on the Learning Outcomes of Class IV Students in Science and Technology Subjects at State Elementary School 047166 Sukadame for the 2023/2024 Academic Year. This research uses quantitative research methods. The population in this study were all fourth grade students at SD Negeri 047166 Sukadame, consisting of 35 students. Sampling used purposive sampling and a Likert scale. The sample involved in this research was class IV students at SD Negeri 047166 Sukadame, consisting of 18 boys and 17 girls. To determine students' initial abilities, researchers conducted a pretest with an average score of 55.6 in the not good category. After researchers used the Student Team Achievement Division Cooperative learning model, it showed that student learning outcomes had increased with an average score of 81.2 in the good category. This research can be proven from the results of calculating the correlation coefficient of 0.631, meaning tcount (0.631) ≥ ttable (0.334). So Ha accepted. So there is a strong influence between the Student Team Achievement Division Type Cooperative Learning model on the Learning Outcomes of Class IV Students at State Elementary School 047166 Sukadame. It can be seen from the results of the t-test, namely 4,671 ≥ 2,060 with a significant level (α = 0.05). thus Ha is accepted. This shows that there is a significant positive influence from the use of the Student Team Achievement Division Type Cooperative Learning model on the Learning Outcomes of Class IV Students at State Elementary School 047166 Sukadame for the 2023/2024 Learning Year.